2003
DOI: 10.1086/377033
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Behavior of Idiosyncratic Volatility*

Abstract: This paper studies the behavior of idiosyncratic volatility for the post war period. Using aggregate idiosyncratic volatility statistics constructed from the Fama and French (1993) three-factor model, we find that the volatility of individual stocks appears to have increased over time. This trend is not solely attributed to the increasing prominence of the NASDAQ market. We go on to suggest that the idiosyncratic volatility of individual stocks is associated with the degree to which their shares are owned by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
5
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(170 citation statements)
references
References 29 publications
(20 reference statements)
8
144
5
2
Order By: Relevance
“…However, this frequency varies substantially, from 0.70% in the 1950s to 15.23% for the 1990s. The increase in volatility is consistent with the increase in crosssectional variation found by McEnally and Todd (1992) from the 1950's to the 1980's and by Xu and Malkiel (2003) across the US markets from the 1950's to 1998.…”
Section: Data Preliminary Findings and Methodologysupporting
confidence: 80%
“…However, this frequency varies substantially, from 0.70% in the 1950s to 15.23% for the 1990s. The increase in volatility is consistent with the increase in crosssectional variation found by McEnally and Todd (1992) from the 1950's to the 1980's and by Xu and Malkiel (2003) across the US markets from the 1950's to 1998.…”
Section: Data Preliminary Findings and Methodologysupporting
confidence: 80%
“…The first is ordinary volatility calculated as a standard deviation of stock returns during the estimation period of (-63;-3). As it is possible to divide stock return volatility into components measuring systematic and unsystematic risk and the latter component called the idiosyncratic volatility captures the firm-specific risk better (Xu and Malkiel, 2003), the following idiosyncratic volatility measure is used in some models: Although in the following analysis the volatility measures are calculated over an estimation period of (-63;-3), these measures are highly correlated (pair-wise correlation coefficients were above 0.79) with other volatility measures calculated for shorter pre-announcement periods (-33;-3) and (-23;-3) and also for periods covering both pre-and post-announcement periods (-30;30); (-20;20).…”
Section: Other Control Variablesmentioning
confidence: 99%
“…Previous studies have found that firm size is positively associated with the level of institutional ownership since institutional investors have a preference for liquid assets. Greater institutional ownership and activities of institutional investors have the effect of increasing the amount of firm-specific information that is incorporated into stock prices (Xu and Malkiel, 2003;Chang and Dong, 2006). On the other hand, however, as in most other emerging markets, many of the larger firms in Turkey form part of some family owned business groups.…”
Section: Analysis Of Resultsmentioning
confidence: 99%